Business Model Canvas as a Means of Entrepreneurship Education at Sangkhom Islam Wittaya School Thailand - Widjayanti, Fefi Nurdiana; Soraya, Zalkha; Burhanuddin, Burhanuddin; Nasrullah, Nasrullah; Ardiansyah, Ardiansyah (Journal of Community Service and Society Empowerment, 2025)
This Community Service Programme (PKM) aims to enhance the entrepreneurial understanding and skills of 30 upper–secondary students at Sangkhom Islam Wittaya School, Thailand, through the application of the Business Model Canvas (BMC) as a learning medium. The background of this activity stems from the school’s need to strengthen entrepreneurship education that is practical and easy for students to grasp. The methods employed include preliminary observation, interactive training, guidance in developing the BMC, and evaluation through students’ project outputs and teachers’ feedback. The results indicate that the students were able to understand the nine elements of the BMC and apply them in designing simple business ideas in a more structured manner. Teachers also acknowledged the effectiveness of the BMC as a tool to support entrepreneurship learning. The contribution of this activity lies in its tangible enhancement of students’ business literacy and creativity through the application of the Business Model Canvas (BMC). It also contributes to strengthening the entrepreneurship curriculum in schools by introducing learning that is more practical, applied, and innovative.